ANALISIS PENERAPAN STRATEGI PEMBELAJARAN AKTIF DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA DI SDN GAPURA BARAT 1 - Ike Yuli Mestika Dewi; Arfin Sabily Putra; Safira Nur Elita; Febi Arista Susilowati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the implementation of active learning strategies in improving student activeness at SDN Gapura Barat 1. A qualitative descriptive approach was employed with 19 third-grade students as participants. Data were collected through prolonged observation, semi-structured interviews, and documentation. Data trustworthiness was ensured through triangulation, member checking, and peer debriefing. Data were analyzed using the Miles and Huberman interactive model and thematic coding. The findings reveal that active learning strategies enhance student participation, confidence, and interaction. Thematic analysis indicates four key dimensions of change: behavioral engagement, cognitive engagement, emotional engagement, and social interaction. The study concludes that active learning fosters a student-centered and meaningful learning environment in elementary classrooms.